SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN KLINIS UNTUK MENENTUKAN TINDAKAN MEDIS PADA PENDERITA PENYAKIT DIABETES MELITUS (STUDI KASUS RSUD dr. Soediran Mangun Soemarso) - , DIAN PRAJARINI; , Ir. Soedjatmiko, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The accuracy of medical treatment to the patients may hamper the patient's recovery. Diabetes mellitus is a disease classified in the group of chronic diseases characterized by elevated levels of sugar in the blood as a result of disturbances in the body's metabolic system, where the organ pancreas unable to produce insulin the body needs. To reduce the medical treatment error required the development of clinical decision support system to determine medical treatment in patients with diabetes mellitus. Clinical decision support system will do the diagnosis of diabetes mellitus type suffered by patients with Bayesian methods, also to determine the complications suffered by patients using forward chaining inference method. Based on a diagnosis of type diabetes mellitus and its complications, it will be given advice appropriate medical treatment. The result of this study is a clinical decision support system to determine medical treatment in patients with diabetes mellitus. In making a diagnosis of diabetes mellitus type, the system capable of delivering confidence level based on Bayesian calculation of data handling before.